Recontextualizing Humor - Tsakona, Villy (De Gruyter Mouton, 2020)
Humor may surface in numerous and diverse contexts, which at the same time determine how humor works, its form, and its functions and consequences for interlocutors. Adopting a sociolinguistic and discourse analytic perspective, this study is aligned with approaches to humor exploring the variety of humorous genres, the wide range of sociopragmatic functions of humor, and the more or less dissimilar perceptions speakers may have concerning what humor is, what it means, and how it works. The chapters of this book propose a new theoretical approach to the analysis of humor by bringing context into focus. Furthermore, the study explores how we can teach about humor within a critical literacy framework creating classroom space for everyday humorous texts that are part of students' social realities, and simultaneously taking into account that humor may yield multiple, disparaging, and often conflicting interpretations. This book is intended to appeal to humor researchers from various disciplines (such as linguistics, media studies, cultural studies, literary studies, sociology, anthropology, folklore) as well as to professionals or researchers in education
10.1515/9781501511929
Keywords: Critical Literacy; Humor; Humorous Genres; Metapragmatics; Metapragmatik; Schriftlichkeit; LANGUAGE ARTS & DISCIPLINES / Linguistics / General